(3JdNjU CYeGd GdMSGHs - (3CHh GdYHGS CMeO Hf eMeO Hf YKeGf GdCROi GdeYQha HGHf GdHfGAs
(3ChdgG (B:s
(3ai gPG GdcJGH JdNjU CYeGd GdMSGH hJbQjH CHhGHg heYGfjg s
(3BNQgG (B:s
(3hdG jbSe GdCOfi ef GdfhYjf Ydi GdCYdi hdGjbSe Ydi GdeSJKfi efg aGage hJOHQ hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B363 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B472s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3QjGVg (B16) s
Keywords: (3GdQjGVjGJs